Raisonner sur des images. Restaurer la Sainte-Anne. - Pierre Leveau (Images Re-Vues)
There is at least one field where scientific and artistic images are similar. It is that of the conservation-restoration of cultural property. From a case study, it is shown that the analogies made in this field by art historians are not conclusions, but premises: they are the indicators of the abductive reasoning which they submit to heritage scientists in the framework of experimental for practical purposes that they make together. The conservators involved on the work are in position to articulate these two perspectives, between art and science. We identify in this article the tipping points from one iconographic regime to another and we model this rack focus, borrowing a few concepts from cinema. The results of this case study will have to be compared with others, in order to deliver semiotics to the conservation experts.